Gambaran Karakteristik Penderita HIV/AIDS di Kabupaten Sumenep Tahun 2018-2019 - Luluk Rofiatul Mafluhah; Nour Athiroh Aboes Sjakoer; Ratna Djuniwati Lisminingsih (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2021)
HIV/AIDS cases have high rates in various countries. The reason is, HIV/AID cases are like an iceberg phenomenon, cases that are not seen and not recorded are more than cases that have been recorded. This study aims to describe the characteristics of HIV/AIDS sufferers in Sumenep District. This study used a descriptive qualitative method with a cross-sectional research design. There were 202 HIV/AIDS sufferers in Sumenep District, while the sample taken was 44 people from 3 Public Health Center. The results showed that based on gender the most were male (57.95%), while the age range was 25-49 years (75.25%), and the area with the most sufferers was Kalianget Sub-District (10.4%) of a total 202 sufferers. Referring to 44 patients who were sampled in this study, there were 39 patients (88.6%) who were married, the most transmission was sex (90.9%), most opportunistic infections were pulmonary tuberculosis (20.4%). Stage I (63.6%) is the most common clinical-stage suffered, and most HIV/AIDS sufferers have been infected for 1-2 years (93.2%). To break the chain of HIV/AIDS transmission, the public needs to be educated, from the mode of transmission to treatment, this also aims to eliminate the negative stigma against people with HIV/AIDS.